Posterior Reversible Encephalopathy Syndrome in Guillain-Barré Syndrome: Just a Problem of Immunoglobulins? Controversy From Two Atypical Case Reports - Belgrado, Enrico; Del Negro, Ilaria; Bagatto, Daniele; Lorenzut, Simone; Merlino, Giovanni; Gigli, Gian L.; Valente, Mariarosaria (Frontiers in Neurology, 2022)
Background Posterior reversible encephalopathy syndrome (PRES), reversible cerebral vasoconstriction syndrome (RCVS) or the coexistence of these two entities share similar risk factors and clinical features. For these conditions a common origin has been supposed. Even if the majority of patients show a favourable course and a good prognosis, a small percentage of cases develop neurological complications. Up to date only about 30 cases of PRES associated to Guillain-Barré syndrome (GBS) have been reported in literature. Cases Here we present two cases of a particularly aggressive PRES/RCVS overlap syndrome, associated with acute motor axonal neuropathy (AMAN) and acute inflammatory demyelinating polyneuropathy (AIDP) variants of GBS respectively, presenting with similar initial clinical aspects and developing both an atypical and unfavorable outcome. On MRI examination the first patient showed typical aspects of PRES, while in the second case radiological features were atypical and characterized by diffusion restriction on the ADC map. The first patient demonstrated a rapid worsening of clinical conditions until death, the second one manifested and maintained neurological deficits with permanent disability. Conclusions We suggest that PRES may conceal RCVS aspects, especially in most severe cases or when associated with a dysimmune syndrome in which autoimmune system and endothelial dysfunction probably play a prominent role in the pathogenesis. Although a role of IVIg treatment in the pathogenesis of PRES has been proposed, we suggest that GBS itself should be considered an independent risk factor for developing PRES.